The mycobacteriophage ms6 lysb n-terminus displays peptidoglycan binding affinity - Gigante, Adriano M. (2022)
Double-stranded DNA bacteriophages end their lytic cycle by disrupting the host cell envelope, which allows the release of the virion progeny. Each phage must synthesize lysis proteins that target each cell barrier to phage release. In addition to holins, which permeabilize the cytoplasmic membrane, and endolysins, which disrupt the peptidoglycan (PG), mycobacteriophages synthesize a specific lysis protein, LysB, capable of detaching the outer membrane from the complex cell wall of mycobacteria. The family of LysB proteins is highly diverse, with many members presenting an extended N-terminus. The N-terminal region of mycobacteriophage Ms6 LysB shows structural similarity to the PG-binding domain (PGBD) of the φKZ endolysin. A fusion of this region with enhanced green fluorescent protein (Ms6LysBPGBD-EGFP) was shown to bind to Mycobacterium smegmatis, Mycobacterium vaccae, Mycobacterium bovis BGC and Mycobacterium tuberculosis H37Ra cells pretreated with SDS or Ms6 LysB. In pulldown assays, we demonstrate that Ms6 LysB and Ms6LysBPGBD-EGFP bind to purified peptidoglycan of M. smegmatis, Escherichia coli, Pseudomonas aeruginosa and Bacillus subtilis, demonstrating affinity to PG of the A1γ chemotype. An infection assay with an Ms6 mutant producing a truncated version of LysB lacking the first 90 amino acids resulted in an abrupt lysis. These results clearly demonstrate that the N-terminus of Ms6 LysB binds to the PG.